Novel core-shell sulfidated nano-Fe(0) particles for chromate sequestration: Promoted electron transfer and Fe(II) production. (December 2021) - Zhu, Xiaowei; Le, Thao Thi; Du, Jiangkun; Xu, Tiantian; Cui, Yayun; Ling, Haibo; Kim, Sang Hoon
Abstract: Sulfidated nanoscale valent iron in form of FeS/Fe (0) shell-core nanoparticle has the aptitude to be a promising remediation material toward reductive removal of metal oxyanions. However, disrupted contact between Fe (0) core and FeS shell by thick iron oxides limited its reactivity improvement, and its mechanism of electron transfer remains unveiled. In this study, a novel sulfidated nZVI core-shell particles (FeS/Fe (0)) was fabricated via a modified post sulfidation approach to achieve a more uniform coverage of FeS for aqueous Cr(VI) sequestration. SEM and STEM tests confirmed the formation of the core-shell FeS/Fe (0) structure with a more solid interaction between FeS layer and Fe (0) core. The highest Cr(VI) removal rate was offered at optimal S/Fe molar ratio of 1/25 that the most chelated Fe 2+ was also observed. The improved performance was due to that FeS shell with greater electronegativity could significantly accelerate the corrosion of Fe (0), facilitate the electron transfer form Fe (0) core to FeS shell according to the electrochemical tests. Moreover, FeS shell provided a protective layer for Fe (0) core so as to alleviate its anoxic passivation in water that FeS/Fe (0) had a better longevity for Cr(VI) removal than nFe (0). Characterizations of STEM and XPS revealed that Cr(VI) was reduced to Cr(III) and evenly coprecipitated with surface Fe(II)/Fe(III). Graphical abstract: Image 1 Highlights: A new FeS/Fe (0) core-shell material was fabricated via "two-step" strategy. The reactivity of FeS/Fe (0) varied with different FeS/Fe (0) atomic ratio. A uniform FeS coverage accelerated election transfer and Fe(II) production for Cr(VI) sequestration.